Constraints faced by Farmers in Adoption of Improved Cultivation practices of Tomato - Sharma, PK; Choudhury, MK; Shekhawat, BS; Prajapati, KA (Journal of Agricultural Extension Management, 2018)
The present paper is based on a study conducted in Matar taluka of Kheda district. The objectives are to study the profile of tomato growers and constraints faced by farmers in adoption of improved cultivation practices of tomato. The constraints were divided into five sub components related to input, financial constraints, marketing, technical and general constraints. After interviewing 100 farmers of ten randomly selected villages, it was revealed that the major constraint related to inputs was unavailability of improved varieties. In case of constraints related to financial aspects it was minimum support price not being declared before sowing season, while in case of marketing, major constraint was unavailability of credit at marginal interest. The major technical constraint was lack of knowledge about export quality produce and among general constraints the major constraint was requirement of more labour